Berkelas: Bersama Eskalasi Kualitas Sosial Pada Masyarakat Desa Karang Dukuh Kabupaten Barito Kuala - Muhammad Audy Renata Putra; Dimas Asto Aji An'amta; Muhammad Wirayuda Suryanata; Ririn Isnaeni Nur; Siti Umriyyah; Mohammad Socheh Ridwan; Haura Nabila; Faula Najmi Soraya (Prodi Sosiologi FISIP ULM, 2023)
Karang Dukuh Village is one of the villages in Belawang District, Barito Kuala Regency, South Kalimantan. The aspects that are highlighted in the service activities in Karang Dukuh Village are agriculture, and culture. Problems such as the lack of interest in learning the practice of female corpse bathing and regeneration of experts for female corpse bathing, the lack of understanding of farmers regarding diseases in rice plants, and education to school students so that a service program is carried out that focuses on teaching the process of female corpse bathing to women in Karang Dukuh Village, socializing tungro disease in rice plants to farmers in Karang Dukuh Village, and giving education conducted to elementary and junior high school students in Karang Dukuh Village. The service was conducted from July 16 to August 21, 2023. The practice of teaching female corpse bathing gave an impact on the understanding of the women of Karang Dukuh village how the procession of female corpse bathing. Socialization of tungro disease in rice plants has an impact on increasing the self-capacity of Karang Dukuh farmers and developing knowledge of diseases in rice plants. Education conducted to school children in Karang Dukuh Village has an impact on increasing knowledge for both elementary and junior high school students. Each program carried out is proven to increase the capacity and ability of the Karang Dukuh Village community and create improvements in community understanding. The long-term impact that will be formed is the quality of the Karang Dukuh community which is getting better.